Extending the toolbox for RNA biology with SegModTeX: a polymerase-driven method for site-specific and segmental labeling of RNA - Raphael Haslecker; Vincent V. Pham; David Glänzer; Christoph Kreutz; Theodore Kwaku Dayie; Victoria M. D’Souza (Nature Communications, 2023)
Abstract RNA performs a wide range of functions regulated by its structure, dynamics, and often post-transcriptional modifications. While NMR is the leading method for understanding RNA structure and dynamics, it is currently limited by the inability to reduce spectral crowding by efficient segmental labeling. Furthermore, because of the challenging nature of RNA chemistry, the tools being developed to introduce site-specific modifications are increasingly complex and laborious. Here we use a previously designed Tgo DNA polymerase mutant to present SegModTeX — a versatile, one-pot, copy-and-paste approach to address these challenges. By precise, stepwise construction of a diverse set of RNA molecules, we demonstrate the technique to be superior to RNA polymerase driven and ligation methods owing to its substantially high yield, fidelity, and selectivity. We also show the technique to be useful for incorporating some fluorescent- and a wide range of other probes, which significantly extends the toolbox of RNA biology in general.